Banker To The Poor: The Story Of The Grameen Bank - Muhammad Yunus; Alan Jolis (London Aurum Press, 2003)
The personal story of the man who founded the system of micro-credit, Banker to the Poor tells the story of how he did it. Today Yunus's system of micro-credit is practiced in some 60 countries, including the US, Canada and France and his Grameen Bank is now a billion-pound business.
Keywords: Nonfiction; Economics; Business; Biography; Poverty; Politics; International relations